If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 2(y + -12) Reorder the terms: y = 2(-12 + y) y = (-12 * 2 + y * 2) y = (-24 + 2y) Solving y = -24 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. y + -2y = -24 + 2y + -2y Combine like terms: y + -2y = -1y -1y = -24 + 2y + -2y Combine like terms: 2y + -2y = 0 -1y = -24 + 0 -1y = -24 Divide each side by '-1'. y = 24 Simplifying y = 24
| 3r+6r=9 | | 3r+6r=16 | | y+37=2y | | 4d+2=42 | | 5w-2w=18 | | 10p-5p=20 | | 2d-d=12 | | q=2(q-19) | | 1/3x=12.85 | | p=2(p-26) | | 18x-24=36-2x | | 10=2/5xn | | q=2(q-41) | | 10=2/5n | | 6m^2-m-7=0 | | X-v=-27+48 | | (13+-2x)4+-2x=16 | | z=2(z-12) | | s+11=2s | | z=2(z-32) | | 16x^2-9=91 | | 2x+50=3y | | (8-4x)3+2x=-108 | | z-7=2z-31 | | (w-2)2= | | 4(3)+3(y)=6 | | 9(12n-6)=15(7n) | | 4(3)+3y=6 | | 2x^2-4x=19 | | (7-3x)3-7x=1 | | x*a=287 | | (2+3x)2+-5x=13 |